The relationship between mathematics self-efficacy and mathematics achievement - Roslan, Samsilah; Hoo, Jacqualine Heap King; Mahyuddin, Rahil; Ahmad Tarmizi, Rohani (Universiti Putra Malaysia Press, 2007)
The purposes of this study was to examine the relationship between mathematics self-efficacy and mathematics achievement for 339 high school students aged between 15 and 17 years. Pearson product-moment correlation showed that mathematics self-efficacy was significantly correlated with mathematics achievement (r=0.30, p< .01). Results showed taht students with higher mathematics self-efficacy were more likely to achieve better mathematics achievement. The finding was generally consistent with the basic assumptions of Bandura's (1986) self-efficacy.